Trade with China and strategy in South American recent economic development - O'Connor, Ernesto A. (coord.) (2012)
Fil: O'Connor, Ernesto A. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina